THE INFLUENCE OF THE LEVEL OF CAPITAL EXPENDITURE, OPERATIONAL EXPENDITURE, AND EXPERTISE CAPABILITIES ON THE TECHNICAL AND ENGINEERING EQUIPMENTAT THE KUALANAMU AIRPORT - Tua M. Lbn. Toruan; Yeni Absah; Isnen Fitri (Adisam Publisher, 2024)
The existence of an airport that serves the need for air transportation modes will have a further effect on the airport as an economic driver and driver, so that the airport is now placed as one of the important parts in the development of an area. Based on a survey of the quality of Kualanamu airport in 2022, unsatisfactory results were obtained for Kualanamu airport. The final score is 4.30 with a standard value of 4.60 where there are low values on several indicators including 3.83 for the free wifi or internet variable, as well as a value of 3.99 for the value of the waiting room air conditioning variable. The purpose of this research is to analyze the level of ability of capital expenditure, operational expenditure and the role of expertise to get the performance of technical and engineering facilities and equipment at Kualanamu airport. This research is a type of quantitative research where quantitative research has the aim of generalizing research findings so that they can be used to predict the same situation in other populations. The instrument used is by distributing questionnaires to 110 respondents and processing data with the SPSS program.